Soy isoflavone intake and stomach cancer risk in Japan: From the Takayama study - Wada, Keiko; Tsuji, Michiko; Tamura, Takashi; Konishi, Kie; Kawachi, Toshiaki; Hori, Akihiro; Tanabashi, Shinobu; Matsushita, Shogen; Tokimitsu, Naoki; Nagata, Chisato (International journal of cancer, 2015)
Although several experimental studies suggested that soy isoflavone intake inhibits the growth of stomach cancer, previous epidemiological studies have observed inconsistent results. We evaluated the associations of soy or isoflavone intake with stomach cancer incidence after considering several lifestyle factors, including salt intake, in a population‐based prospective cohort study in Japan. Subjects were 14,219 men and 16,573 women aged 35 years or older in September 1992. Soy and isoflavone intakes, assessed with a validated food‐frequency questionnaire, were controlled for the total energy intake. Cancer incidence was mainly confirmed through regional population‐based cancer registries. Until March 2008, 441 men and 237 women developed stomach cancer. After adjustments for multiple confounders, a significantly decreased relative risk of stomach cancer was observed in the highest vs. lowest quartile of soy intake; the estimated hazard ratios were 0.71 (95% CI: 0.53, 0.96) for men (p for trend = 0.039) and 0.58 (95% CI: 0.36, 0.94) for women (p for trend = 0.003). Similar inverse associations between isoflavone intake and stomach cancer risk were also observed in women. Higher intake of non‐fermented soy foods was significantly associated with a lower risk of stomach cancer (p for trend: 0.022 in men and 0.005 in women), whereas there was no significant association between the intake of fermented soy foods and a risk of stomach cancer. These results suggest that a high intake of soy isoflavone, mainly nonfermented soy foods, have a protective effect against stomach cancer. What's new? Soy food is a good source for isoflavones, which are substances with known anti‐oxidative and cancer‐protective properties. In this prospective epidemiological study conducted in Japan, the authors detected a lower risk of stomach cancer in people who consumed larger amounts of soy food and thus isoflavones, underscoring how diet can influence this frequent cancer type in Japan. Interestingly, a reduction in cancer risk was only observed for nonfermented and not for fermented soy foods. Fermented soy food, i.e., miso, is rich in salt, itself a possible cause of stomach cancer and the authors speculate that this could have confounded previous studies yielding ambiguous results.